(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Due to the pandemic, the learning system has changed drastically from traditional face-to-face classes to virtual classes. Virtual classes are more challenging than face-to-face classes, especially for housekeeping services of BSHM students in terms of utilizing proper tools and equipment, as demonstrated during virtual classes. Factors such as the learning environment, internet connection or mobile data greatly affect the learning of students who take virtual classes. Students attending virtual classes depend on watching videos on YouTube to gain knowledge and gather ideas. Meanwhile, to comply with some requirements, students share, contribute, or utilize other resources to possess proper tools and equipment for virtual demonstrations, as school laboratory facilities are unavailable. Despite the challenges students encountered in virtual classes, the Bachelor of Science in Hospitality Management at Bestlink College of the Philippines provided significant reasons why individuals should not be sceptical about enrolling in one of their core courses, Housekeeping. Students will understand the important role of Housekeeping in the hospitality industry. They will discover new sanitation procedures under the New Normal. They will master the technical skills and knowledge as a housekeeping trainee. Students will also comprehend Housekeeping’s work systems, workflow, and business procedures. Furthermore, they will learn to manage and avoid mistakes in making decisions in the Housekeeping Department. Therefore, this study aims to explore the impact of virtual classes in housekeeping services on hospitality management students to enhance their service skills and knowledge of the proper usage of tools and equipment. This research study used a qualitative method, which investigates attitudes, behaviour, and experience through interviews, focus group discussions, observations, and documentation or online journals that interact less with the respondents. A purposive sampling technique was used by the researchers to distribute the questionnaire. The questionnaire was given to 100 second-year college students of the BSHM Department at Bestlink College of the Philippines, composed of male and female students, to gather information and data. The researchers utilized an online survey questionnaire as an instrument in the study conducted. The researchers gathered information and ideas related to the research study through articles, newspapers, local and foreign literature and studies related to the study. The researchers did an online pre-test survey of the questionnaires to ten BSHM second-year college students taking virtual classes at Bestlink College of the Philippines who were not part of the sample. The purpose of online pre-testing was to analyze whether the questionnaire had unclear items. The outcome was considered as the editing and revisions of the final questionnaire. The researchers also sought permission from the Bachelor of Science in Hospitality Management Program Head at Bestlink College of the Philippines to conduct this study. The researchers personally administered and retrieved the questionnaire to ensure 100% retrieval. The research used statistical formulas such as percentage, frequency, and weighted mean to interpret the data tables based on the gathered information through the questionnaire. Meanwhile, a five-point Likert scale was also used to describe the extent of the existence of the conditions as perceived by the respondents.